Jobs, Access to Credit, and Informality in MENA Countries - Brancati, Emanuele (World Bank, Washington, DC, 2022)
This paper explores the link between jobs, access to Finance, and informality. Using longitudinal firm-level data for countries in the Middle East and North Africa, it documents that jobs creation is positively associated with access to finance. At the same time, the findings show that access to finance is lower for firms that are more exposed to competition from informal firms. As a possible mechanism underlying this result, the paper provides evidence that firms that suffer informal competition have worse expectations on future sales growth, which in turn are associated with fewer loan applications.